Arquitectura e industrialización de la construcción en la obra de João Filgueiras Lima – Lelé (2016)
The industrialization of a building requires high technical rigor in design and production. In Brazil, the architect João Filgueiras Lima, “Lele” stands out as an example of the design process of industrial buildings, covering all stages of construction. This article provides the technological trajectory of Lele and development of industrial production through their diverse experiences in factories for the performance of building systems. Then, its little known industrialized production in the Community Support Framework Ribeirao Preto (Sao Paulo, Brazil), is analyzed. As a method, a single case study was used, with multiple sources of evidence such as interviews, direct observation and documents. From the results, it seems that “Lele” constantly improved construction practices and industrial elements used since it participated in the entire process of building construction. Although use of mass production is done, you get an appropriate method for the context in which the complex buildings are inserted.